2022
DOI: 10.1002/cjce.24355
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled double‐loop FOIMC‐PD control architecture for double integral with dead time processes

Abstract: A novel double‐loop control configuration with two controllers is suggested for double integrating processes with dead‐time. The stabilizing range of the inner‐loop proportional‐derivative (PD) controller is obtained using the Routh stability criteria. From this range, the exact PD settings are obtained by following a graphical approach where the integration of absolute error (IAE) is plotted for different PD settings. The PD settings resulting in the minimum IAE are chosen. In addition to stabilizing the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In case of G 00 p2 s ð Þ, offset is observed in process response for MSP scheme developed by Kumar et al 14 Table 5 shows the performance indices (IAE, ITAE, ISE, ITSE, and TV) which further validate the supremacy of the proposed scheme in comparison with the settings provided in earlier studies. 14,15 Through simulation experiments, it is found that maximum 10% delay perturbation is allowable for the proposed scheme. Small gain theorem 35 is employed towards robust stability analysis (Table 2) while incorporating positive perturbations as shown in Figure 12.…”
Section: Model IIsupporting
confidence: 58%
See 4 more Smart Citations
“…In case of G 00 p2 s ð Þ, offset is observed in process response for MSP scheme developed by Kumar et al 14 Table 5 shows the performance indices (IAE, ITAE, ISE, ITSE, and TV) which further validate the supremacy of the proposed scheme in comparison with the settings provided in earlier studies. 14,15 Through simulation experiments, it is found that maximum 10% delay perturbation is allowable for the proposed scheme. Small gain theorem 35 is employed towards robust stability analysis (Table 2) while incorporating positive perturbations as shown in Figure 12.…”
Section: Model IIsupporting
confidence: 58%
“…Responses clearly reveal that the proposed scheme provides superior closed-loop performance, especially during load rejection phases. It is to note that the settings by Kumar et al 14 fail to regain the desired output with the perturbed model G 00 p1 s ð Þ subsequent to the load change. Robust stability analysis results are exhibited in Table 2 with small gain theorem 35 in the presence of positive perturbations (ΔK p and Δθ m ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations